New type of phase transition in gravitational theories - Camanho, Xián O. (2012)
We set forth a new type of phase transition that might take place in gravitational theories whenever higher-curvature corrections are considered. It can be regarded as a sophisticated version of the Hawking-Page transition, mediated by the nucleation of a bubble in anti-de Sitter (AdS) space. The bubble hosts a black hole in its interior, and separates two spacetime regions with different effective cosmological constants. We compute the free energy of this configuration and compare it with that of thermal AdS. The result suggests that a phase transition actually occurs above a certain critical temperature, ultimately changing the value of the cosmological constant. We discuss the consistency of the thermodynamic picture and its possible relevance in the context of AdS/CFT. © 2012 American Physical Society.